Main Pathological Changes of Benign Ureteral Strictures - Tan, Jiang; Yu, Zhuoyuan; Ling, Xinyi; Qiu, Guoping; Yang, Xin; Tang, Yi; Yang, Dong; Yang, Mei; Gao, Fei (Frontiers in Medicine, 2022)
Objective: To identify the pathological classification of benign ureteral strictures according to the histological features and explore the relationship between various pathological types and inflammatory cells, fibroblasts, and collagen. Patients and Methods: 31 specimens from patients diagnosed with ureteral strictures between 2013 and 2021 were included and classified according to the histopathological characteristics. The number of fibroblasts and inflammatory cells was counted, and the proportion of type I and type III collagen in ureteral stricture tissues was detected by picrosirius red staining. Results: We identified three types of benign ureteral strictures in 31 specimens: inflammatory cell infiltration (n=10, 32%), fibroplasia (n=14, 45%), and hyalinization (n=7, 23%), with significant differences in obstruction history and hydronephrosis grades among the three types. The number of inflammatory cells (lymphocytes, neutrophils and eosinophils) was significantly lower in hyalinization ureteral strictures than in the other two types(p<0.05). The number of foreign-body giant cells associated with foreign-body reactions increased significantly in suture-induced ureteral strictures(p<0.05). Fibroplasia type had the largest number of fibroblasts, whereas the other two types had smaller numbers. The results of type I and III collagen analysis showed that type I and III collagen were the most abundant in hyalinization among all ureteral stricture types (p<0.05). Compared to ureteral strictures, the content of type I and III collagen in atresia increased significantly(p<0.05). Conclusion: Common pathological types of benign ureteral strictures include inflammatory cell infiltration, fibroplasia, and hyalinization. Changes in type I and III collagen, inflammatory cells, and fibroblasts in different pathological types may be related to the progression of ureteral strictures.